1981
DOI: 10.1111/j.1423-0410.1981.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange in the Management of Patients with Multiple Sclerosis: Preliminary Observations

Abstract: Since humoral factors have been implicated in the pathogenesis of multiple sclerosis (MS) and previous attempts at therapeutic intervention have not met with uniform success, plasma exchange (PE) was recently proposed for the management of this disease. We are currently investigating the possible effectiveness of PE in the treatment of MS, and to date 6 patients have been entered into the study. At least 4 of our patients who did not respond to conventional therapy have shown unequivocal, moderate to marked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Others did not demonstrate a benefit [7][8][9][10] including two randomised, blinded, sham controlled studies [7,8]. However reports on the value of plasma exchange for severe, acute MS relapses that are resistant to steroid therapy [11][12][13] have been more promising. Similarly case reports of successful use of plasma exchange in other episodes of severe, inflammatory demyelinating CNS disease, including acute disseminated encephalomyelitis (ADEM) [14][15][16] and Devic's syndrome [17] suggest that plasma exchange could be useful across the full spectrum of severe acute inflammatory demyelinating CNS disease.…”
Section: Introductionmentioning
confidence: 95%
“…Others did not demonstrate a benefit [7][8][9][10] including two randomised, blinded, sham controlled studies [7,8]. However reports on the value of plasma exchange for severe, acute MS relapses that are resistant to steroid therapy [11][12][13] have been more promising. Similarly case reports of successful use of plasma exchange in other episodes of severe, inflammatory demyelinating CNS disease, including acute disseminated encephalomyelitis (ADEM) [14][15][16] and Devic's syndrome [17] suggest that plasma exchange could be useful across the full spectrum of severe acute inflammatory demyelinating CNS disease.…”
Section: Introductionmentioning
confidence: 95%
“…This study also demonstrated very elegantly that PE brings about an activation of the immune system and suggested the possible need for adjunctive immunosuppression to control antibody production in autoimmune diseases with subacute relapsing or chronic disease when PE is employed as a therapeutic modality. There are other anecdotal reports of marked improvement following PE in patients with acute attacks of MS or other severe demyelinating diseases of the CNS (6–15).…”
Section: Plasma Exchange In Acute Msmentioning
confidence: 99%
“…Duplicate platelet concentrates from individual donors were stored at 22 and 4°C, respectively. At time O and at 24-hour intervals, pH, 02 and C02 tensions, ADP-induced aggregation, glass adhesivity, hypotonic shock response (HSR) and NEM-induced lipid peroxidation were measured.A highly significant correlation between NEM-induced lipid peroxidation and HSR was established, which suggests that the former method can be used for the in vitro prediction of posttransfusion survival of preserved platelets.platelet in vivo posttransfusion survival by Lundberg and Murphy [8], Kim and Baldini [7] and Valeri et al [15].Since we could recently confirm the va lidity of Stuart's nonradioisotopic technique [13] for the determination of platelet life span in vivo [14], we extended the evalua tion of N-ethyl-maleimide (NEM)-induced lipid peroxidation to platelet concentrates to investigate its possible use in assessing plate let viability in stored concentrates. Parallel studies have been performed to investigate the correlation between NEM-induced lipid peroxidation and HSR which is normally explored in our platelet quality control pro gram.…”
mentioning
confidence: 55%
“…In the main series of experiments, we as sessed our working conditions by recording pH, p02 and pC02, ADP-induced aggrega tion and glass adhesivity of platelets stored as concentrates, and measured the HSR and NEM-induced lipid peroxidation in 20 plate let concentrates each stored at 22 and 4 °C for 24, 48 and 72 h. The aim of this study was to investigate the correlation between HSR and MDA production in stored plate lets, since the HSR has been reported to cor relate with platelet posttransfusion survival [7,8,14], mental conditions. Figure 1 furthermore re veals that it was significantly dependent on the storage temperature.…”
Section: Resultsmentioning
confidence: 99%